THE VALUE OF SUCCESS CHARACTERS IN THE PREVENTION OF PSYCHOLOGICAL DISORDERS IN THE PANDEMIC TIME COVID-19 (Overview of the Al-Qur'an Surat Al-'Ashr) - Al Halik; Sukma Sari Dewi Chan (Universitas Islam Ahmad Dahlan, 2021)
The increasing spread of Covid-19 has made this new virus a major concern of the world community, so it's no wonder that in the timeline until news on the topic of the corona is always found. Receiving excessive information can affect a person's psychological and physical health. People who are unable to filter incoming information can cause thoughts of stress, anxiety, fear, and excessive worry, which can lead to psychological changes in their mental health. The purpose of this study is to contribute steps to prevent psychological disorders during a pandemic by following the values ​​of the successful characters in QS. Al-Ashr. The research was conducted using a library research approach, following systematic steps starting from collecting, processing, and concluding the findings data. Successful character values ​​can be taken as steps to prevent psychological disorders during the Covid-19 pandemic from QS. Al-Ashr, namely: having faith, doing good deeds, advising each other in truth, and advising each other to be patient. Internalizing these four characters, a person will benefit greatly and be saved from losses such as endless stress, anxiety, and worry.